Electrocoagulation of commercial naphthalene sulfonates: Process optimization and assessment of implementation potential - Olmez-Hanci, Tugba; Kartal, Zeynep; Arslan-Alaton, İdil (Journal of Environmental Management, 2012)
The commercially important naphthalene sulfonate K-acid (CHNOS; 2-naphthylamine 3,6,8-tri sulfonic acid) was subjected to electrocoagulation employing stainless steel electrodes. An experimental design tool was used to mathematically describe and optimize the single and combined influences of major process variables on K-acid and its organic carbon (COD and TOC) removal efficiencies as well as electrical energy consumption. Current density, followed by treatment time were found to be the parameters affecting process responses most significantly, whereas initial K-acid concentration had the least influence on the electrocoagulation performance. Process economics including sludge generation, electrode consumption, and electrochemical efficiency, as well as organically bound adsorbable halogen formation and toxicity evolution were primarily considered to question the feasibility of K-acid electrocoagulation. Considering process economics and ecotoxicological parameters, process implementation appeared to be encouraging.